Total Factor Productivity Growth and Job Turnover in Mexican Manufacturing Plants in the 1990s - Angel Calderon-Madrid; Alexandru Voicu (Institute for the Study of Labor (IZA), 2004)
This paper analyzes the performance of Mexican manufacturing firms following trade liberalization within a very specific institutional setting: The North American Free-Trade Agreement (NAFTA). We compare plants' productivity growth and patterns of job creation and destruction across their relative degree of integration into foreign product markets, their access to technology, and behavior with respect to research and development. Our findings show that access to imported inputs is the more significant vehicle for productivity enhancing effects of trade openness. Investment in technology is, by far, most strongly correlated with plant productivity. Like productivity, job turnover at firm level is strongly influenced by the degree of integration in international markets, import competition, and R&D behavior.
Keywords: C14; G63; F13; D24; O54; 330; total factor productivity; NAFTA; R&D; job creation and destruction; Produktivität; Arbeitsmobilität; Industrielle Forschung; Aussenhandelsliberalisierung; Beschäftigungseffekt; Schätzung; NAFTA-Staaten; Mexiko